Ender’s Game: Use of Anti-Bildungsroman Convention to Explore the Impact of Child Exploitation - Ko, Audrey Sarang (Advances in Social Sciences Research Journal, 2025)
This paper provides a detailed reading of the way in which anti-bildungsroman conventions in Orson Scott Card's Ender's Game have been utilized to critique the institutional exploitation of children and the psychological consequences that follow. In contrast to traditional bildungsroman stories, which show the protagonist's self-determined growth, Card subverts the genre by characterizing Andrew "Ender" Wiggins as a child genius whose development is controlled by manipulation, isolation, and militarization. The main research question of the paper is as follows: What are the anti-bildungsroman conventions that Card uses in Ender's Game to portray the use of children as instruments of the institution and the complex effects such action has on them? The essay will contextualize this question with the three main stages in Ender's story: first, his determined and tormenting early life; second, his enforced development at Battle School; and third, the post-war period wherein he bears the gnawing sense of guilt and suffers a split identity. This piece points out that Card has managed to achieve this mainly through some narrative techniques such as fragmentation, different viewpoints, and ironic reversals of coming-of-age conventions. The text discusses how Ender's journey is a critique of the institutions and power. Ender's childhood is not a place to have new experiences, but a space of trauma; the Battle School is a setting where children are psychologically trained, isolated from each other and desensitized; and by showing Ender being forever scarred by the abusive processes, the book's ending negates the common image of a bildungsroman's happy conclusion. The paper contends that Ender's Game stands as both a dystopian piece of fiction and a political treatise. Card emphasizes the ethical dilemmas of the act of childhood as a weapon against humanity, disclosing the far-reaching emotional and psychological effects of using children as pawns for the institutional good. The text, therefore, becomes a mirror that reflects real-life situations involving child combatants and youth exploitation, consequently, the book emphasizes the price of turning children into a resource for utility over innocence.